Reducing Settlement Using Piled Raft for Neighboring Foundations in Port-Said (Port Said Engineering Research Journal, 2013)
The problems of building settlements in Port-Said area have been a great concern in recent years. Damages occur inbuildings due to urban development that requires high rise structures to accommodate these extensions. Raft has beenused for many new buildings in Port-Said. Soft to firm clay layers extends down to depths reaching 60 m under theground surface. This paper studies the effect of constructing new building beside an existing one. Piled raft has beenstudied as settlement reducer and thus to be used as a foundation system in the new building. The typical soilstratification and properties in Port-Said zone are considered in this study. Parametric study is carried out to examineinfluence of new piled raft variables on the existing building. It has proved that the use of piled raft reducesconsiderably settlement under the existing building.